Trade Shocks in Brazil: An Investigation of Effects on Regional Manufacturing Wages - Filipe Lage-De-Sousa (European Regional Science Association (ERSA), 2006)
Brazil has experienced two trade shocks in the 90's: unilateral liberalization, which weighted average nominal tariff reduced from 37.7% in 1988 to 10.2% in 1994; drastically real devaluation of 47% in the exchange rate in 1999. These two effects has influenced the location of industry in Brazil, since the industry center of Brazil, Sao Paulo State, reduced its participation in the industry sector from 52% in 1985 to 43% in 2002. This occurs when the dispersion forces overcome the agglomeration ones. The main dispersion force evidenced by the literature is the increase of competition, not only in the goods market (a new product), but also in the factor market (demand of labor, which increases wages). In a trade agreement, the most common trade shock, these two forces occurred simultaneously. At this case, it is possible to distinguish between two dispersion forces: competition of the imported goods (first shock); competition in the labor market (second shock). One way to evaluate these effects can be by investigating the effectiveness of transport cost to understand the regional differences in wages and if it has reduced (or increased) its explanation power after the trade shock. In order to do that, the methodology of Hanson 1997 will be used as a basic framework. It is possible to analyze the effects of these trade shocks in the disparities of regional wages in Brazil with his methodology. However, there will be some differences to his framework. First, Hanson uses state level data and this paper has a more disaggregated regional data (microregion, which divides Brazil into more than 500 parts). Second, Hanson doesn't take into account any change in educational level, infrastructure improvement or government intervention, which are considered in this investigation. The first results show that transport cost is important to understand differences in wages between Brazilian microregions and trade shocks have influenced in some sense these disparities, but not so consistently as transport costs. Moreover, it seems that dispersion force of the second shock was greater than the first one, therefore, competition to hire new employees expel more plants to lower wages regions than comptetion with new products.
Keywords: 330